Effects on neuroprotection and α-synuclein expression of a Canna coccinea rhizome extract - Spotorno, Viviana Graciela; Roxo, Mariana; Wetterauer, Bernhard; Zabal, Osvaldo Alfredo; Wink, Michael (Elsevier, 2025)
Parkinson's disease (PD) is the second most common neurodegenerative disorder in the elderly, currently with no cure. Its mechanisms are not well understood, however α-synuclein protein aggregation plays a central role in the pathogenesis of PD, leading to neurodegeneration. We demonstrated that in a PD model dietary in Caenorhabditis elegans treatment with an extract from the rhizome of Canna coccinea decreased the accumulation of α-synuclein. The extract showed low toxicity to neuro 2a cells and protected them from oxidative damage with H2O2 as a model for neurodegeneration. We studied the chemical profile of the extract using liquid chromatography couple to Mass Spectrometry. In order to characterize the herbal extract, we quantified rosmarinic acid as a marker compound and measured its antioxidant activity in vitro. Altogether, apart from its potential as a functional food, Canna coccinea may be an interesting source of secondary metabolites in the development of potential novel anti-neurodegenerative drugs.